Arabic Learning in New Normal Era for Students with Visual Impairment at Inclusive Madrasah: Ta’līm al-Lugah al-’Arabiyyah fi al-Fatrah al-Jadīdah liṭullāb Żawi al-‘I’āqah al-Baṣariyyah fi al-Madrasah al-Syāmilah - Yuslam, Yuslam; Harimi, Abdal Chaqil; Anggraeni, Annisa Juli (Study Program of Arabic Language Teaching, 2023)
This study examines the process of learning Arabic at MAN 2 Sleman which is committed to inclusive education so that they integrate learning for students with disabilities and non-disabled students. This type of research is qualitative research with a phenomenological approach. The techniques used in collecting data are observation, interviews, and documentation. The data sources selected in this study were the Head of the Madrasah, Arabic Teachers, Students with Disabilities, and the Head of ULD. Purposive and snowball sampling is used in determining the data source. The results of this study indicate that MAN 2 Sleman always strives to be committed to providing inclusive education. This is evidenced by the effort to complete physical facilities such as guiding blocks and the establishment of ULD in 2020. In addition, MAN 2 Sleman always increases the capacity for knowledge, understanding, and educational practice for HR in the madrasa by organizing various training or workshops for the MAN 2 community. Sleman, the formation of inclusive friends and assistance for students with visual impairments after the covid-19 pandemic. Specific problems in the Arabic learning process for students with disabilities are the lack of Arabic language teachers' ability to write and read Braille Arabic letters, the absence of Arabic references in braille form, and the unavailability of an Arabic dictionary either in braille form or an easily accessible application, by students with disabilities. Efforts made to overcome these problems are the provision of recordings of books or materials and even Arabic questions that teachers or friends of non-disabled students carry out. Students with disabilities can write Latin in the maharah Kitabah or Arabic and then be corrected by a companion who can write and read Arabic Braille. In addition, even though the COVID-19 pandemic has been considered sloping, applications are still ongoing, such as recording text readings or Arabic questions using VN, using the YouTube application to help deepen material and using Google Form media to answer Arabic questions.